(untitled) (Journal of Educational Sciences, 2017)
In the article we envisage the issues formation of future educational psychologists in penal institutions on the basis of Al-Farabi Kazakh National University. Marked features of activity of the psychologist in penal institutions. They relate to the provision of psychological support of students of closed institutions with a view to their reintegration and resocialization for life. This activity of school psychologist updated with the development of the juvenile system in Kazakhstan. It gives a detailed analysis of importance studying some obligatory disciplines in formation educational psychologists to work in penal institutions. The article touches upon the issue of necessity increasing practical knowledge in penal institutions for future educational psychologists. Also in article are described some results of survey students of philosophy and political science faculty. As proposals, the authors propose the development of individual educational trajectory, aimed at the training of teachers-psychologists to penal institutions.